2020
DOI: 10.1186/s13550-020-0611-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, radiation dosimetry, acute toxicity and automated synthesis of [18F]AmBF3-TATE

Abstract: Introduction: [ 18 F]AmBF 3 -TATE is a somatostatin agonist that selectively binds to somatostatin receptor subtype 2 (SSTR2). For clinical translation, pharmacokinetics, radiation dosimetry, and acute toxicity of [ 18 F]AmBF 3 -TATE were assessed with good laboratory practice (GLP) standards. Methods: ICR mice were intravenously administered 0.8-2.0 MBq of [ 18 F]AmBF 3 -TATE, with one group pre-injected with 100 μg of [ 19 F]AmBF 3 -TATE 30 min before radiopharmaceutical administration to assess uptake speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 16 publications
1
16
0
7
Order By: Relevance
“…Further optimization of the radiochemical synthesis is essential for future clinical use; however, the success of the optimization of labeling [ 18 F]-AmBF 3 -TATE for clinical assessment bodes optimism in this regard. 41 In vitro competitive binding assays showed that both BL08 and BL09 had low nanomolar binding affinities to CXCR4 comparable to LY2510924. In xenograft models, both tracers demonstrated high tumor uptake and rapid clearance from peripheral tissues to provide high-contrast PET images of CXCR4.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further optimization of the radiochemical synthesis is essential for future clinical use; however, the success of the optimization of labeling [ 18 F]-AmBF 3 -TATE for clinical assessment bodes optimism in this regard. 41 In vitro competitive binding assays showed that both BL08 and BL09 had low nanomolar binding affinities to CXCR4 comparable to LY2510924. In xenograft models, both tracers demonstrated high tumor uptake and rapid clearance from peripheral tissues to provide high-contrast PET images of CXCR4.…”
Section: ■ Discussionmentioning
confidence: 99%
“…These results underscore the suitability of [ 18 F]­PepBF 3 for preclinical in vivo imaging experiments. Further optimization of the radiochemical synthesis is essential for future clinical use; however, the success of the optimization of labeling [ 18 F]­AmBF 3 -TATE for clinical assessment bodes optimism in this regard …”
Section: Discussionmentioning
confidence: 99%
“…i. ), was auf eine hohe Stabilität der B-18 F-Bindung hindeutet [90]. Der Tracer zeigte in AR42J-Tumortragenden Mäusen eine schnelle Pharmakokinetik und ermöglichte die Darstellung des Tumors in hohem Kontrast [89].…”
Section: F-markierungsstrategien Basierend Auf Borverbindungenunclassified
“…Obwohl die Radiomarkierung meist manuell durchgeführt wird, sind Protokolle für die vollautomatische Produktion nach den Regeln der guten Herstellungspraxis von 89 Zr-markierten mAbs auf einem kommerziell erhältlichen Synthesemodul beschrieben worden [115]. Aus Sicht der anorganischen Chemie ist DFO nicht das ideale Koordinationsmolekül für 89 Zr, da DFO ein hexadentater Chelator ist, der aus 3 Hydroxamateinheiten besteht, während Zr 90 Y-und anderen Lanthaniden-Radiometallen [120,121]. Im letzten Jahrzehnt hat sich 177 Lu als eines der nützlichsten Radionuklide für die Entwicklung von Endoradiotherapeutika herausgestellt, insbesondere für die Behandlung von kleinen oder mittelgroßen Tumorläsionen [121][122][123].…”
Section: Zirkonium-89unclassified
“…69 Lau et al developed an automated synthesis with 400 mL reaction (containing 200 nmol of precursor) and achieved molar activity of 435 + 162 GBq/mmol (n ¼ 3) with starting activity of *150 GBq. 62 Droplet radiochemistry techniques provide a way to dramatically reduce this reaction volume and precursor amount (and provide an automated way to do so). Using a Teflon-glass chip reactor, the reaction was performed in a 5 mL reaction volume (5 nmol of precursor), and molar activity up to 144 GBq/mmol was observed with starting activities as low as 0.93-1.1 GBq.…”
Section: High Molar Activitymentioning
confidence: 99%